Short-term influence of Immufen™ on mild allergic rhinitis: a randomized, double-blind, placebo-controlled study - K, Mamatha; Aryan, Manu Kanjoormana; Prabhakaran, Prathibha; Mulakal, Johannah Natinga; Das S, Syam; IM, Krishnakumar; Parameswara Panicker, Sreejith (Frontiers in Allergy, 2024)
IntroductionAllergic rhinitis (AR) is an IgE-mediated reaction to inhaled allergens, and is a prominent health concern affecting approximately 400 million people worldwide. A comprehensive understanding of AR's pathophysiology is imperative for developing novel therapies, especially considering its frequent co-morbidity with asthma and conjunctivitis. The escalating prevalence of AR is correlated with increased urbanization and environmental pollutants, recognized as prominent contributing factors. Dysregulation in immune networks, Th1/Th2 cytokine imbalance, activation of mast cells and eosinophils are implicated in AR progression. Classic AR symptoms include nasal congestion, nasal itching, rhinorrhea, and sneezing which significantly impact the quality of life, social interactions, and workplace productivity.MethodsThis randomized, double-blind, placebo-controlled, three-arm, three-sequence study was aimed to assess the efficacy of supplementation of a co-delivery form of turmeric extract with ashwagandha extract (CQAB) in comparison with a bioavailable curcumin (CGM) and placebo in alleviating AR symptoms and enhancing the quality of life in individuals with mild AR. Participants received either placebo, CGM, or CQAB twice/day for 28 days, and subjective measures were recorded at the baseline and at the end of study.ResultsCQAB supplementation demonstrated a significant (P < 0.05) improvement in Total Nasal Symptom Score (TNSS) compared to placebo and CGM. Furthermore, CQAB administration resulted in enhanced sleep quality (P < 0.05) as evaluated by the BIS questionnaire, heightened energy levels, and decreased fatigue and overall mood disturbance (POMS-SF) compared to both placebo and CGM.ConclusionThe results suggests that CQAB has the potential to be used as a dietary supplement in alleviating AR discomforts.Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/login.php; Identifier CTRI/2021/01/030355.